Combining liquidity usage and interest rates on overnight loans: an oversight indicator - Tatu Laine; Tuomas Nummelin; Heli Snellman (Bank of Finland, 2011)
This study utilises payment system data to analyse market participants liquidity usage and to trace interest rates paid on overnight loans. Our aim is to examine how liquidity usage has changed during the years 2006 2/2011 and to combine this information with data on overnight lending rates between market participants. It turns out that the Furfine algorithm used in the analysis produces overnight interest rates that correlate very closely with the EONIA curve. Based on Finnish payment system data, we identify four separate time periods: normal, start of turmoil, acute crisis and stabilizing period. The results show that, during the acute crisis period, TARGET2 participants holding an account with the Bank of Finland paid, on average, lower overnight interest rates than other banks in the euro area. However, the results reveal there has been some lack of confidence between Finnish participants since the onset of the financial crisis. A new indicator the Grid which we present here shows this very clearly. We suggest that this new indicator could be a highly useful tool for overseers in supporting financial stability analysis.
URN:NBN:fi:bof-20140807183
Keywords: 330